Potensi dan Tantangan Tanaman Transgenik bagi Ketahanan Pangan Indonesia (Sebuah Tinjauan Literatur) - Christin H. Bonnu (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Food security initiatives face significant challenges due to surging demand outpacing food supply, compounded by climate change and extreme weather events. Biotechnology innovations, particularly transgenic crops, offer a potential solution. As genetically modified organisms (GMOs), transgenic crops are engineered to enhance agricultural productivity and could play a pivotal role in mitigating Indonesia's food crisis. In this context, crops developed through genetic modification technologies are a promising approach to address Indonesia's food security challenges. The present investigation evaluates the feasibility of adopting these transgenic solutions while considering their advantages and limitations. This research was conducted in March 2025 using a narrative literature review method that began by collecting references from Google Scholar, including studies relevant to the opportunities and challenges of GMO crop development in Indonesia, and extracting data from these studies to be presented in narratives and tables. This literature review found that transgenic crops have the potential to support food security through the creation of agricultural commodities with better productivity, adaptive to biotic and abiotic stresses, and higher nutritional content, achieved by utilising the most advanced genetic engineering technologies. Meanwhile, challenges that limit the application of GMO crops relate to biosafety, regulatory, socio-economic, and ethical aspects, and public trust.